An Attitude to Investigate Exergy and Energy Performance of Thermal Power Plant in Iraq - Hayder R. Shaheed, Raoof M. Radhi, Hayder Noori Mohammed (Mathematical Statistician and Engineering Applications, 2022)
Despite its availability of fossil fuels, which is the basic energy source used to generate electricity, Iraq still suffers from a shortage of electric power supplies, given that most of their existing steam power does not operate at their designed production capacities and thus reduces its production efficiency. An energy and exergy analysis of the Mossaib steam plant, built in the 1980s and has a production of (1200) MW rated output, can help identify the locations of losses and discover the components that will facilitate the development of the station if work is carried out to maintain, develop, and improve its efficiency and preserve energy sources. In Engineering Equations Solver (EES), a code is built to estimate energy loss, energy efficiency, rate of energy and exergies, second law efficiency, and exergy destruction for each part of the plant by considering the actual value range of operating parameters. The analysis focuses on the sources of exergy destruction that occur in the plant components, revealing that the highest destruction occurs in the boiler, followed by the high-pressure (HP) turbine, then the low-pressure (LP) turbine, and then the condenser. Finally, the intermediate pressure (IP) turbine shows the least exergy destruction compared with other turbines.